Psychological Capital and Innovative Behavior: Examining the Mediating Role of Organizational Support - Dhruba Prasad Subedi; Dilli Ram Bhandari (International Journal of Asian Business and Management, 2024)
This study examines the influence of psychological capital on innovative behavior of managerial level employees of star rated hotels in Kathmandu valley emphasizing the mediating role of organizational support. To achieve the stated objectives, descriptive and casual comparative research design was used.  The data were collected from the primary source using a structured questionnaire administered through convenience sampling technique. The respondents comprised 205 managerial level employees working in different departments of star hotels in Kathmandu, Nepal. The Process macro 4 Hayes, (2022) was used for analyzing the structural relationships among the constructs. The findings reveal that psychological capital has no significant effect on innovative behavior of employees. Furthermore, the study finds that organizational support mediates the relationship between psychological capital and innovative which may be achieved by providing resources, encouragement, and a conducive environment. This study highlights the mediating role of organizational support to enhance the innovative behavior of employees. The outcomes of the study explore how organizational support mediates the relationship between Psychological Capital and innovative behavior, providing new insights into the mechanisms that drive innovation in the workplace. The findings can help managers fostering strong organizational support which significantly enhance the innovative behavior of employees. Managers should focus on creating a supportive work environment that nurtures employees' psychological capital to drive innovation and maintain a competitive edge.  To enhance the generalizability of this research, it would be beneficial to include a larger sample size, particularly from larger companies. Expanding the study to include international perspectives and utilizing a mixed-method approach could also provide deeper insights to the study